Indicators of Human Resources Controlling - Nowak, Marta (Wskaźniki controllingu zasobów ludzkich, 2011)
The paper presents the author's own concept of human resources controlling measurement. It covers the subject of performance measurement of the field of human resources management. The author presents her own solutions, including the HR controlling indicators and methods of their comparisons.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 116-126
Keywords: human resources management; human recourses; controlling; performance measurement; indicators